Carbon stocks across different environments, disturbance regimes, and stand age in Fitzroya cupressoides forests, the longest-lived species of the southern hemisphere - González, Mauro E.; Lara, Antonio; Urrutia-Jalabert, Rocío; Bustos-Salazar, Angela; Ruiz-Gómez, Carolina; Aravena, Juan C. (Frontiers in Forests and Global Change, 2022)
Forest disturbances influence Fitzroya forest structure and carbon stocks at multiple spatial and temporal scales. Natural disturbances such as landslides and volcanism affect and give origin to the mostly pristine Fitzroya stands present in the Andean cordillera. On the other hand, mostly human-caused fires and logging have been the main processes shaping the structure of Fitzroya stands in the Coastal range and of Fitzroya small remnants in the Central depression. The main goal of this study was to assess the carbon stocks and accumulation rates of Fitzroya forest stands according to their development stage under different disturbance regimes and environmental conditions given by the three physiographic units where the species grows (Coastal range, Central depression and Andean range). The site selection included an age sequence of stands, known as chronosequence approach. We identified Fitzroya post-disturbance stands in three different stages of development: Young forest stage (main cohort ≤ 200 year old), Mature forest stage (200 to 800 year old), and Old-growth forest stage (800-1500 year old). The following biomass components were considered: living standing trees, dead standing trees (snags) and logs laying on the ground (coarse woody debris). Old-growth Fitzroya forests reached a mean total carbon stock (standing live trees, snags and coarse woody debris) of 507, 279, and 331 Mg C ha-1 in the Andean and Coastal ranges, and Central depression, respectively. Fitzroya cupressoides contributes in average more than 80% to the total carbon stock in the Andean and Coastal ranges, and 63% in the Central depression. The remainder corresponds mainly to Nothofagus spp. The high carbon stocks in old-growth stands in the Andean range are explained by Fitzroya longevity and larger size, wood decay resistance and the low recurrence of volcanic events. Carbon accumulation rates differ between the forests in the three physiographic units (Central depression>Andean range>Coastal range), mainly due to the different growth rates and environmental conditions present in each unit. In the context of climate change, conserving old-growth stands with large biomass and carbon stocks and restoring Fitzroya forests should be recognized as a key contribution towards national and global goals to mitigate global warming.